Associations of Long-term PM10 Exposure with Mortality in Dialysis Patients: A Population Based Cohort Study - Shih-Feng Chen; Yu-Hui Chien; Yu-Chin Lai; Pau-Chung Chen (Aerosol and Air Quality Research)
Abstract Exposure to PM2.5 has been observed to be associated with an increased risk of mortality in dialysis patients, while sporadic studies have hinted at the adverse effects of coarse particulate matter (PM10) on kidney health. However, the impact of PM10 on survival in end-stage renal disease patients remains unclear. To address this gap, we conducted a retrospective cohort study, linking the Taiwan Air Quality-Monitoring Database (TAQMD) with the National Health Insurance Research Database (NHIRD) based on patients’ zip codes. We included 34,088 adult dialysis patients living in areas with ambient measurements of PM10, NO2, CO, and SO2 between 1 January, 2000 and 31 December, 2013. We used a multivariate Cox proportional hazards model to estimate mortality risk and observed that each interquartile range (IQR) increase in the mean PM10 concentration during follow-up period was associated with a 13.2% higher risk of mortality (adjusted hazard ratio [aHR] = 1.132, 95% confidence interval [CI] = 1.097–1.169). Even in two-pollutant scenarios, the association between long-term exposure to PM10 and mortality remained significant. Spline analysis demonstrated a non-linear concentration-response relationship between PM10 and mortality, with an increase in aHR when the average PM10 exposure exceeded a threshold of 43 µg m−3. Stratification analysis revealed that male patients had a significantly higher increase in mortality risk per IQR increase in PM10 compared to female patients (aHR 1.185 vs. 1.074; p-interaction < 0.001). Our study demonstrated a significant association between long-term ambient PM10 exposure and mortality risk among dialysis patients, especially in males. A non-linear concentration-response relationship between PM10 and mortality was noted, with mortality risk increasing when the mean PM10 surpassed a specific threshold. The PM10-mortality association persisted after considering co-exposures to other air pollutants. These findings strongly indicate a positive association between long-term ambient PM10 exposure and mortality among dialysis patients.